2018
DOI: 10.1186/s40478-018-0615-0
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Toxic Oligomeric Assemblies of RNA-binding Protein: Musashi in Alzheimer’s disease

Abstract: Alzheimer’s disease (AD) is the most common neurodegenerative disorder associated with structural and functional alterations of brain cells causing progressive deterioration of memory and other cognitive functions. Recent studies demonstrate that several neurodegenerative diseases, including AD exhibit RNA-binding proteins (RBPs) pathologies, including TAR DNA -binding protein (TDP-43), fused in sarcoma (FUS), superoxide dismutase (SOD1) and T-interacting antigen-1 (TIA-1), highlighting the role of RBPs in neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 56 publications
2
33
0
Order By: Relevance
“…The filter trap assay was performed using a Bio-Dot SF microfiltration apparatus (Bio-Rad), as described previously ( 48 , 80 , 90 ). Briefly, 1 μg of each end-product reaction was applied onto nitrocellulose membranes, previously prewetted in TBS with very low Tween 0.01% (TBS-T), through the use of a vacuum-based bio-slot apparatus.…”
Section: Methodsmentioning
confidence: 99%
“…The filter trap assay was performed using a Bio-Dot SF microfiltration apparatus (Bio-Rad), as described previously ( 48 , 80 , 90 ). Briefly, 1 μg of each end-product reaction was applied onto nitrocellulose membranes, previously prewetted in TBS with very low Tween 0.01% (TBS-T), through the use of a vacuum-based bio-slot apparatus.…”
Section: Methodsmentioning
confidence: 99%
“…Musashi-1 is a particularly interesting RBP. Its roles in mediating stem cell regeneration and cell differentiation are well-known [25], and recent evidence suggests it may be implicated in neurodegenerative diseases [26,27], as have the prominent RBPs TDP-43 and FUS [28,29]. The removal of Musashi-1 s IDR prevents this protein's recruitment to stress granules that reduce the chemoresistance of some types of cancer cells [30,31].…”
Section: Of 14mentioning
confidence: 99%
“…We previously reported that the cellular localization of MSI1 and MSI2 in human AD cortical tissues is found in the cytoplasm and nuclei of mature neurons (Sengupta et al, ). In this scenario, we demonstrated that tau oligomers (TauO) interact with the MSI proteins in AD brains, and that MSI proteins are able to form oligomers in vitro (Sengupta et al, ). Clarifying their cell compartment location and regulation is an important step to identifying MSI’s crucial roles in the pathogenesis of AD.…”
Section: Introductionmentioning
confidence: 99%